Brand resonance and brand salience in luxury cosmetic products with symbolic value as the mediating variable - Pristiana Widyastuti (Journal of Enterprise and Development (JED), 2023)
Purpose — Intense competition compels every product to innovate. Luxury brands must employ various strategies to attract consumers, one of which is fostering strong customer relationships, measured by the extent of customers' connection to the brand. This study aims to conduct a more in-depth analysis of the cosmetic luxury brand, using brand resonance as the dependent variable, brand salience as the independent variable, and symbolic value as the mediating variable.Method — This research employs an explanatory research design with a quantitative approach. The study's population consists of consumers of luxury cosmetic brands in Indonesia, with a sample size of 96 respondents. Data analysis is conducted using Partial Least Squares (PLS), a variant of Structural Equation Modeling (SEM) capable of performing both model testing and structural model testing simultaneously. The statistical tool employed for this analysis is SmartPLS 4, which provides user-friendly access to multivariate analysis methods.Result — The results indicate that brand salience does not have a significant effect on brand resonance. However, it was found that symbolic value can serve as a mediator in the relationship between brand salience and brand resonance. Brand resonance is a crucial aspect of maintaining consumer loyalty and can be achieved by strengthening the brand's association with customers.Contribution — This research contributes by examining the influence of brand salience on brand resonance, a less-explored aspect of brand management, and introduces the concept of symbolic value as a potential mediator.